2014 IEEE Globecom Workshops (GC Wkshps) 2014
DOI: 10.1109/glocomw.2014.7063537
|View full text |Cite
|
Sign up to set email alerts
|

Device-to-device assisted two-stage cooperative multicast with optimal resource utilization

Abstract: Device-to-device (D2D) communication has the potential to facilitate wireless multicast by retransmissions among users in proximity to each other. In this paper, the D2D assisted cooperative multicast (CM) is investigated in a new scenario, where a large number multicast recipients are densely distributed within a small area (called a D2D cluster). In this scenario, D2D multicast is innovatively employed in the retransmission stage, and a new relay selection scheme named nearest center protocol (NCP) is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Both a dense model (with a finite network area) and an extended model (with a finite density) are considered. A similar two-phase multicasting scheme has been also studied by taking into account fairness between users or energy efficiency (see, e.g., [14], [15] and references therein).…”
Section: Multicasting Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both a dense model (with a finite network area) and an extended model (with a finite density) are considered. A similar two-phase multicasting scheme has been also studied by taking into account fairness between users or energy efficiency (see, e.g., [14], [15] and references therein).…”
Section: Multicasting Optimizationmentioning
confidence: 99%
“…The time allocation between the two phases was investigated in [17], which showed that more time should be dedicated to the second phase as the UEs move away from the BS. Finally, a similar two-phase cooperative scheme with multiple antennas at the BS was proposed in [24] in the context of broadcasting under perfect CSIT.…”
Section: Introductionmentioning
confidence: 99%
“…As the received signal will arrive from different sources, there may be a problem of synchronization. However, some cyclic prefix coding (CPC) schemes can be used to combine the signals arriving from different sources [19]. As long as the delay among all the cluster heads is less than one cyclic prefix, all the received signals at the cluster members can be added up to make a stronger signal.…”
Section: Related Workmentioning
confidence: 99%